2018
DOI: 10.2196/10971
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Evaluation of eHealth Interventions: Systematic Literature Review

Abstract: Background Until now, the use of technology in healthcare is driven mostly by the assumptions about the benefits of eHealth rather than the evidence of it. It is noticeable that the magnitude of evidence of effectiveness and efficiency of eHealth is not proportionate to the number of interventions that are regularly conducted. Reliable evidence generated through comprehensive evaluation of eHealth interventions may accelerate the growth of eHealth for long-term successful implementation and help to experience … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 62 publications
5
104
0
5
Order By: Relevance
“…Although useful work has been performed by these previous authors, no single source is able to provide clear guidance in selecting appropriate evaluation approaches in relation to the specific evaluation phases of eHealth. Therefore, to enhance quality and safety, and to facilitate long-term implementation of eHealth solutions into daily practice, raising the awareness of eHealth evaluators about the wide array of eHealth evaluation approaches and thereby enhancing the completeness of evidence is sorely needed [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although useful work has been performed by these previous authors, no single source is able to provide clear guidance in selecting appropriate evaluation approaches in relation to the specific evaluation phases of eHealth. Therefore, to enhance quality and safety, and to facilitate long-term implementation of eHealth solutions into daily practice, raising the awareness of eHealth evaluators about the wide array of eHealth evaluation approaches and thereby enhancing the completeness of evidence is sorely needed [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study tried to minimize these limitations by using a scoping review of available literature including consultation exercise. [ 5 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…The pieces of evidence for assessing the actual benefits of e-health programs are lacking and, moreover, for which there is no standard framework for assessing the actual benefit of these digital health ventures. [ 5 ] A large number of e-health system which is being deployed give rise to the importance of the new pragmatic framework to demonstrate the benefits of these program and guide adaptation decision. There are plethora of different kinds of literature that have been proposed to assess the e-health system but pieces of evidence about their actual implementation in a real-world scenario are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The question is which level of evidence is necessary prior to widespread use of digital health apps[ 89 ]. A systematic literature review of the evidence-based evaluations, conducted by Enam et al[ 90 ], revealed that a lack of standardization of eHealth interventions is a substantial barrier to assessing the full potential of eHealth interventions. Standardization could significantly improve the quality of intervention studies and, furthermore, could also ease the implementation of eHealth interventions.…”
Section: Challengesmentioning
confidence: 99%